Genetic Expression Screening of Arsenic Trioxide-Induced Cytotoxicity in KG-1a Cells Based on Bioinformatics Technology - Li, Yahui; Feng, Yingjie; Si, Xiaohui; Zhao, Chenjin; Wang, Fanping; Niu, Xinqing (Frontiers in Genetics, 2021)
Acute myeloid leukemia (AML) is a malignant tumor of the hematopoietic system, and leukemia stem cells are responsible for AML chemoresistance and relapse. KG-1a cell is considered a leukemia stem cell-enriched cell line, which is resistant to chemotherapy. Arsenic trioxide (ATO) is effective against acute promyelocytic leukemia as a first-line treatment agent, even as remission induction of relapsed cases. ATO has a cytotoxic effect on KG-1a cells, but the mechanism remains unclear. Our results demonstrated that ATO can inhibit cell proliferation, induce apoptosis, and arrest KG-1a cells in the G2/M phase. Using transcriptome analysis, we investigated the candidate target genes regulated by ATO in KG-1a cells. The expression profile analysis showed that the ATO had significantly changed gene expression related to proliferation, apoptosis, and cell cycle. Moreover, MYC, PCNA, and MCM7 were identified as crucial hub genes through protein–protein interaction network analysis; meanwhile, the expressions of them in both RNA and protein levels are down-regulated as confirmed by quantitative polymerase chain reaction and Western blot. Thus, our study suggests that ATO not only inhibits the expression of MYC, PCNA, and MCM7 but also leads to cell cycle arrest and apoptosis in KG-1a cells. Overall, this study provided reliable clues for improving the ATO efficacy in AML.